Preparation and properties of antibacterial polyhexamethylene biguanide/palygorskite composites as zearalenone adsorbents - Kang, Y. R.; Mu, B.; Zhu, G.; Zhu, Y. F.; Wang, A. Q.
Due to the environmental problems derived from the use of common surfactants as modifiers for clay mineral adsorbents to mitigate mycotoxin contamination of animal feeds, finding non-toxic modifiers to prepare safe and efficient adsorbents is necessary. The objective of the present study was, therefore, to modify acidified palygorskite with polyhexamethylene biguanide (PHMB)to obtain antibacterial polyhexamethylene biguanide/palygorskite (PHMB/Plg)composites for the removal of zearalenone, a common mycotoxin. The PHMB/Plg composites were characterized and analyzed by X-ray diffraction, Fourier-transform infrared spectroscopy, field-emission scanning electron microscopy, and isothermal nitrogen adsorption analysis. The adsorption properties of the composites with respect to zearalenone and their antibacterial activity with respect to Escherichia coli and Staphylococcus aureus were studied. The results indicated that the hydrophobicity of palygorskite was enhanced after modification with PHMB, which could effectively improve the adsorption property of palygorskite toward the nonpolar zearalenone molecules. The adsorption capacity of PHMB/Plg increased with increasing amounts of polyhexamethylene biguanide and increasing pH. The adsorption data were described well by pseudo-second order kinetics and by the Langmuir adsorption model. The maximum adsorption capacity was 2777 ?g/g. When the amount of PHMB added increased to 15 wt.percent , the composites obtained exhibited good antibacterial performance, and the minimum inhibitory concentrations for Escherichia coli and Staphylococcus aureus were both at 2.5 mg/mL.
Keywords: ANTIBACTERIAL ACTIVITY; COMPOSITE ADSORBENTS; PALYGORSKITE; POLYHEXAMETHYLENE BIGUANIDE; ZEARALENONE